2015
DOI: 10.6009/jjrt.2015_jsrt_71.12.1201
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Study on Dose Reduction Using Iterative Reconstruction in Low-dose Computed Tomography for Lung Cancer Screening

Abstract: We investigated dose reduction ability of an iterative reconstruction technology for low-dose computed tomography (CT) for lung cancer screening. The Sinogram Affirmed Iterative Reconstruction (SAFIRE) provided in a multi slice CT system, Somatom Definition Flash (Siemens Healthcare) was used. An anthropomorphic chest phantom (N-1, Kyoto Kagaku) was scanned at volume CT dose index (CTDIvol) of 0.50-11.86 mGy with 120 kV. For noise (standard deviation) and contrast-to-noise ratio (CNR) measurements, CTP486 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, it is worth to note that the LDCT protocol combined with iDose 4 was practiced as reference standard instead of fulldose protocol with FBP reconstruction in our study, considering iDose 4 , the hybrid IR, has already been used routinely with robust reconstruction speed, as well as the hybrid IRs such as iDose 4 , sinogram-affirmed iterative reconstruction, and adaptive statistical iterative reconstruction were observed yielding diagnostic image quality in LD chest CT with similar dose setting at around 1 mSv. 13,17,18 Our study has several limitations. First, a relatively small number of positive cases were reviewed in the study.…”
Section: Nodule Detectionmentioning
confidence: 95%
“…In addition, it is worth to note that the LDCT protocol combined with iDose 4 was practiced as reference standard instead of fulldose protocol with FBP reconstruction in our study, considering iDose 4 , the hybrid IR, has already been used routinely with robust reconstruction speed, as well as the hybrid IRs such as iDose 4 , sinogram-affirmed iterative reconstruction, and adaptive statistical iterative reconstruction were observed yielding diagnostic image quality in LD chest CT with similar dose setting at around 1 mSv. 13,17,18 Our study has several limitations. First, a relatively small number of positive cases were reviewed in the study.…”
Section: Nodule Detectionmentioning
confidence: 95%
“…For example, the clinical studies have typically been based on subjective visual scoring of quality (7,21,22,24,26) and the phantom studies have been based on the measurement of physical image characteristics such as noise and/or resolution (1,6,13,15). Under the formalism established by International Commission on Radiation Units and Measurements report 54 (27), image quality is defined as the effectiveness by which an image can be used for its intended task.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that IR techniques help improve image quality and retain diagnostic value of LDCT at substantially reduced radiation dose [6][7][8].…”
Section: Low-dose Ct For Lung Cancer Screeningmentioning
confidence: 99%